Increased serum thioredoxin levels are not correlated with executive functions in children with attention deficit hyperactivity disorder. (13th July 2019) - Guney, Esra; Buyuktaskin, Dicle; Tas Torun, Yasemin; Arslan, Burak; Gulbahar, Ozlem; Ozaslan, Ahmet; Isik Taner, Yasemen; Iseri, Elvan
Highlights: Significantly higher Trx levels were found in children with ADHD. No correlation between serum Trx levels and executive functions. Trx levels had no relationship to the disease severity measured by CTRS. Impaired oxidative mechanisms in ADHD may lead to increased Trx levels. This is the first study investigating the serum levels of Trx in ADHD. Abstract: The first step of this study aims to determine whether thioredoxin (Trx) has a potential role in attention deficit hyperactivity disorder (ADHD) by measuring serum Trx levels in children with ADHD. In the second step, this study aims to reveal whether there is any relationship between Trx and executive functions. This is the first study investigating the serum levels of Trx in children with ADHD. This study sample included 45 patients diagnosed with ADHD and 30 healthy controls. Conners Teacher Rating Scale (CTRS) and Behavior Rating Inventory of Executive Function (BRIEF) are used to evaluate ADHD presentation, severity and executive functions, respectively. Trx levels were measured using an enzyme-linked immunosorbent assay (ELISA) kit. Significantly higher Trx levels were found in children with ADHD. No significant correlations were found between serum Trx levels and executive functions for controls or ADHD group; although hyperactive/impulsive ADHD presentation showed positive correlations with some subdomains of executive function. Serum Trx levels and disease severity, measured by CTRS, showed non-significant correlations. This study may be the first step in the study of the role played by Trx and oxidative stress in ADHD, further research is needed to support these preliminary findings.